KONFLIK PERAN DAN KELELAHAN EMOSIONAL SEBAGAI PREDIKTOR KOMITMEN AFEKTIF GURU SEKOLAH DASAR - Dian Lestari Siregar; Raymond Raymond (Universitas Batam, 2026)
This study examines the effects of role conflict and emotional exhaustion on the affective commitment of elementary school teachers working in the hinterland islands of Batam City, Indonesia. A quantitative explanatory design with a cross-sectional survey approach was employed. The study involved 100 elementary school teachers selected using proportionate stratified random sampling from schools located in Belakang Padang, Bulang, Galang, and other hinterland islands. Data were collected using a five-point Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that role conflict had a negative and significant effect on teachers’ affective commitment (β = −0.274; t = 2.746; p = 0.006). Emotional exhaustion also had a negative and significant effect on affective commitment (β = −0.492; t = 5.183; p < 0.001). Emotional exhaustion was identified as the more dominant predictor of affective commitment. Role conflict and emotional exhaustion collectively explained 48.7% of the variance in teachers’ affective commitment. These findings indicate that conflicting job demands and depleted emotional resources can weaken teachers’ emotional attachment, involvement, and sense of belonging toward their schools. Therefore, school leaders and local education authorities should establish clearer and more proportionate task allocation, strengthen organizational support, improve educational and transportation facilities, and provide psychological well-being programs tailored to the geographical characteristics of hinterland schools.